A importância do lúdico no ensino: aprendizagem da educação básica nos anos iniciais - Bona, Clarice Strapasson Desengrini (2012)
By paying attention to the specialized literature, it is noticed that the use of playfulness in the learning of basic education, in particular of the early years, is significant. Therefore, the present study aims to highlight the importance of playfulness as a facilitator of learning in classroom. It will be emphasized the importance of the playful concerning the oriented sociability aspect of children, with help of technology to show playful exercises as an important role both in life and in training of children as in the life of their educators. In this way, it is highlighted the need to demystify that plays are not just mere entertainment, but means in which learning and children are developed considering their imaginative capacity and wondrous. The school should facilitate learning using fun activities that create a dynamic and creative environment through games, jokes, musicality, among other ways.